EFFECTS OF 25GMS/KG, 50GMS/KG AND 75GMS/KG OF BODY WEIGHTS OF GARCINIA CAMBOGIA PLANTS ON BLOOD GLUCOSE LEVELS OF DIABETIC RATS—-AN ANIMAL MODEL STUDY. - Kashif Rasheed Shaikh1 , Kausar Amir2 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Type 2 Diabetes Mellitus (T2DM) affects an estimated 462 million people worldwide, accounting for roughly 6.28% of the world’s population. OBJECTIVE: The study is aimed to determine the potential effects of alternative medicine in the management of T2DM as many medicinal plants and its product have traditionally been used since ancient time and one such medicine plant is Garnicia Cambogia that belongs to the family Clusiaceae widely known as Malabar Tamarind. Hence, the present study is aimed to determine the effects of ancient medicine approach by using Garnicia Cambogia plant extract in the management of T2DM in animal model. METHODOLOGY: A total number of n=100 Wistar rats were divided into five groups. Rats were procured from the Basic Medical Sciences Institute’s Open Market/Animal House at JPMC Karachi. While housing and handling the rats, the researchers scrupulously adhered to the rules established in the NIH Guide for the Care and Use of Laboratory Animals. RESULTS: The negligible P-value (P = 0.57) supports this conclusion, demonstrating that there was no significant variation in body weight between the rat groups. The fact that the rat groups had equal baseline body weights eliminates any study bias and allows for a more accurate comparison and interpretation of the experimental data. CONCLUSION: The study suggests that Garcinia Cambogia plant extract has favourable benefits on blood glucose levels and glycemic control in an animal model of type 2 diabetes, especially at higher dosages.